NILAI EKONOMI DAN KONTRIBUSI HUTAN RAKYAT BAMBU (Bambusa sp) (Studi Kasus di Desa Telagah, Kecamatan Sei Bingai, Kabupaten Langkat) ECONOMIC VALUE AND CONTRIBUTION OF PEOPLE BAMBOO FOREST (Bambusa sp) (Case Study at Telagah Village, Sub District of Sei - Ricardo Felixon Simatupang; Siti Latifah; Yunus Afifuddin (Program studi Kehutanan USU, 2013)
Bamboo (Bambusa sp) is a forest plant that has many benefits but is not yet used by forest communities widely. This study aims to determine patterns of distribution, economic value and contribution of Bamboo. This research was using purposive sampling technique. Based on research conducted bamboo evenly to the patterns of distribution and the dominant grows at an altitude of 700-1100 mdpl, while the highest economic value of bamboo is Rp. 9.450.000/year and the lowest economic value is Rp. 810.000/year, while the highest contribution of Bamboo to people’s income is 33,40% and the lowest contribution of Bamboo is 4,84% Keywords: Bamboo, Distribution Pattern, economic value, contribution, income